Existe uma literatura para bebês? - Cristiene de Souza Leite Galvão (2016)
This paper is inserted on the Language and Education research line of the postgraduate program in Education from the Faculty of Education of the Federal University of Minas Gerais - UFMG and it aims at investigating the literary content in literature books for kids under 2 years old. For this purpose, it tries to establish approximations with the child-like universe, considering babies as subjects that are products and producers of culture and that, on the exchange of experiences with others and with their environment, build their singularities. The analysis of the literary works for babies presents itself as a great challenge, since children within this age group are taking their first steps towards their assortment of the world. The so much needed abstraction for children to be able to create other worlds in other times and spaces, common in the fictional text, is still not reliable on works for this age group and this leads to particular differences in the publications for this audience. Can these books be labelled as literary books? Can babies produce meanings when in contact with fictional narratives? To answer such questions, the support of theoretical views is needed. Such views consider childhood as an event and babies as subjects that compose themselves in the language and through which (what means do) they subjectify and share their experiences. The option of knowing and analysing child literature books for babies aims at categorizing them according with their interlocutory proposal and interlinking them with the Vigotskian, Wallonian and Golsean perspectives of amplifying the childrens affective and cognitive experiences, taking into account the peculiarity of this age group. Bernardo, Compagnon, Eagleton, Jouve are, as well, important interlocutors of this research since they resize the strictu senso concept given to literature, a much needed attitude for the apprehension of the plurality of works that exist today. Also amplifying this concept, authors such as Hunt and Sosa help to configure the specificity of literary texts destined to children. The corpus of analysis was selected from a personal library and it intended to embrace the diversity of production for this age group. The following categories were raised: materiality, theme, genre, number of words and concept of the work. The results indicate that, while inside a broader concept of literature, it is possible to classify books for children as literary books, since the moment when the rupture with reality is materialized, not as a transcription, but as a (re)presentation of what is real. Even though a lot of books for babies do not present a narrative structure, it is possible to see the fracture with what is real and a fictional exercise capable of creating tension of many different colours and tones.